Integrated control of neglected tropical diseases in Brazil: document review of a national campaign in light of WHO recommendations - Rosa Castália Ribeiro Soares; Amanda Gabriela de Carvalho; João Gabriel Guimarães Luz; Ana Luiza Zílio Lucas; Eliane Ignotti (Revista Panamericana de Salud Pública, 2023)
Objective. To describe the results of a national campaign aimed at the integrated control of neglected tropical diseases in Brazil in light of the World Health Organization (WHO) official documentation related to the integration of strategies for the prevention, control, and elimination or eradication of neglected tropical diseases. Methods. A document review that included official WHO documents published between 2007 and 2020 and campaign results extracted from the official technical report produced by the Brazilian Ministry of Health. Results. The integrated control of neglected tropical diseases was gradually incorporated in the WHO documentation over time. Preventive chemotherapy through mass drug administration, intensified case management, and integrated vector management were extensively recommended as strategies for integrated control. The Brazilian campaign was carried out in four iterations between 2013 and 2017. Children aged 5 to 14 years enrolled in municipal public schools nationwide were targeted. In summary, a total of 1 074 and 73 522 new cases of leprosy and trachoma, respectively, were detected. Nearly 18 million doses of preventive chemotherapy for soil-transmitted helminthiasis were administered. More than 700 cases of schistosomiasis were diagnosed and treated. Conclusions. The integrated strategies implemented in Brazil throughout the campaign generated results aligned with the WHO recommendations for the control of neglected tropical diseases, especially those regarding mass drug administration, active case detection, and intensified case management. Therefore, the continuity of the campaign with adequate evaluation tools must be encouraged as a constant public health policy in the Brazilian government agenda.